Testy zgodności dotyczące rozkładów wykładniczych typu Kołmogorowa-Smirnowa - Domański, Czesław (The Goodness of Fit Tests for Kolmogorov-Smirnov Exponential Distributions, 2007)
The paper presents tests verifying hypothesis stating that the population distribution is exponential. We will limit ourselves to the presentation of a couple of tests based on the Kolmogorov-Smimov and Cramer-von Misses statistics. The tests' power is presented for a few alternative distributions for n = 20 and n = 50. In the light of the results presented the Cramer-von Misses test generally turns out to be more powerful.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 76-82